PENDIDIKAN KARAKTER DI MADRASAH TSANAWIYAH HASAN JUFRI BAWEAN - Nurul Huda (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2016)
The purpose of this study was to determine the role and responsibilities of teachers in implementing character education in MTs Hasan Jufri Bawean. This research is a field research using descriptive-qualitative approach. The study population consisted of all teachers of MTs Hasan Jufri totaling 40 people, and the sample 20 subject class IX teachers. Methods of data collection in this study using the method of observation, interviews and documentation. The results of the research are the facilities with considerable learning, extracurricular activities, the role of teachers in regular activities, such as the implementation of Duha prayer and prayer dhuhur congregation, spontaneous activities, such as giving sanction to students who are late, and create slogans that can affect students for good character, have been lead learners noble personality which all domains of aspects aimed to implement the teachings of Islam, both in attitudes, skills, and deeds of each learner.